The mitochondrial genome of Murina huttoni rubella (Chiroptera: Vespertilionidae) from China. Issue 1 (1st January 2016) - Zhang, Qiuping; Cong, Haiyan; Yu, Wenhua; Kong, Lingming; Wang, Yingyong; Li, Yuchun; Wu, Yi
Abstract: Murina huttoni rubella is a common Murina species in China, with a medium forearm length and reddish brown hairs. In this study, based on a male M. h. rubella individual from Jiangxi, China, its complete mitochondrial genome was sequenced and analyzed. The genome is 16, 707 bp in length, including 22 tRNA genes, two rRNA genes, 13 protein-coding genes and a control region. The composition and arrangement of genes are similar to other bats. Phylogenetic trees that covered all released complete mitochondrial genome of bats were constructed using Bayesian Inference and maximum likelihood methods. Both phylogenetic results showed that M. h. rubella and M. ussuriensis have closer phylogenetic relationship. The complete mtDNA genome sequence of M. h. rubella would provide valuable information for solving taxonomic and phylogenetic problem in future.